Language in thought and action - Hayakawa, S. I. (Samuel Ichiyē), 1906-1992.; Hayakawa, Alan R. (San Diego : Harcourt Brace Jovanovich, 1990)
Introduces the principles of semantics, explains how language works, and how an understanding of semantics is useful in everyday life situations.
Includes bibliographical references (p. [182]-187) and index.
Wilson's Public Library.
Wilson's Senior High School.
Wilson's Public Library, May 2002.
Wilson's Senior High School, November 2002.
Young Adult.
Keywords: English language -- Semantics; English language; Semantics